Resiliensi akademik dan dukungan sosial teman sebaya sebagai prediktor academic adjustment pada mahasiswa baru fakultas kedokteran Universitas X Surabaya - Afifah, Nindya Rahmalia; Arya, Lutfi; Rahmania, Andi Maulida (Fakultas Psikologi Universitas Hang Tuah, 2025)
This study aimed to examine the relationship between academic resilience and peer social support with academic adjustment among first-year medical students at the Faculty of Medicine, University X Surabaya. The transition from high school to university often required substantial adaptation to changes in curriculum, learning methods, and academic expectations. These conditions posed challenges for new students to adjust to the dynamics of university life and the increasing complexity of academic demands. The study employed a quantitative correlational approach using a simple random sampling technique that involved 125 students from the 2024 cohort. Data were collected through Google Forms using three instruments: the Academic Resilience Scale with 18 valid items, the Peer Social Support Scale with 47 valid items, and the Academic adjustment Scale with 42 valid items. The results showed a significant relationship between academic resilience and peer social support with academic adjustment. Partially, academic resilience contributed, while peer social support contributed. These findings emphasized that students’ academic adjustment was influenced not only by individual resilience but also by positive social support within their peer relationships.